Gender mainstreaming in basic education of the City of Mati, Southern Mindanao, Philippines - Jeralyn Hemillan-Sacro; Mary Fil M. Bauyot; Jhonnel P. Villegas (Davao Research Journal)
The integration of gender-responsive teaching strategies in public schools remains to be a challenge among educators. This social issue entails more in-depth investigation, especially in primary public education, to promote gender-responsive instruction and increase inclusiveness in education. This study aimed to assess the level of gender mainstreaming efforts of public elementary and secondary schools in the City of Mati, employing the Gender Mainstreaming Evaluation Framework (GMEF). A quantitative design through purposive sampling methods where the respondents are the GAD focal persons was used in this study. The study found out that the Department of Education (DepEd) Schools Division in the City of Mati’s level of gender mainstreaming is still in the Foundation Formation stage (Stage 1). There's a long way to integrate gender into its systems, programs, and services. The study recommends that the agency may craft policies to attain the maximum level of mainstreaming efforts and be modeled and replicated by other agencies in the future.